Pelaksanaan Administrasi Kepegawaian Di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Ciamis - Budi Nugraha; Mafturrahman Mafturrahman; Aghus Jamaludin Kharis; Eliza Wulan Nur Oktaviana; Winarsih Winarsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
this study focuses on Human Resource Administration at the Office of Human Resources and Human Resource Development Ciamis Regency. The purpose of this study is for the implementation of Human Resources Administration at the Office of Human Resources and Human Resources Development Ciamis Regency. In this study, a qualitative descriptive method is used which is a study designed to describe the atmosphere of a location based on observation data, actions, language and text. Based on the observations made in this study, the observation of the authors can be concluded that the implementation of Human Resource Management to the agency for Human Resource Development and Human Resources Ciamis Regency is still less than optimal. Some employees are not distributed according to their area of expertise or expertise. The process of work performed is less than optimal and the results of the work are not good enough. The recruitment process is also less than optimal and can have a bad impact on the institution and the organization itself. The assignment of employees must be carried out in accordance with their individual abilities. The misalignment of the employee with his area of expertise and skills can have a significant impact on which agency to hire in the future.